The effect of monetary incentives on promoting weight loss in individuals with obesity - Assim A Alfadda; Norah A Alsaber; Amr S Moustafa; Shaffi A Shaik (Wolters Kluwer Medknow Publications, 2020)
Objectives: This study evaluated the effect of a cash reward program on promoting weight loss and whether this effect will last after 1 year of follow-up. Materials and Methods: This is a retrospective analysis of a 4-month program that provides cash reward for losing weight. The study individuals were weight loss program participants, aged 18-65 years, reached after 1 year (n = 162). Participants were categorized according to their main reason for joining the program as follows: those for whom incentive was the primary reason to enroll (incentive-motivated) and those who participated mainly to lose weight regardless of the incentive (self-motivated). Results: There was a significant weight loss in all participants at the end of the 4-month program compared with that at baseline (89.49 ± 18.86 vs. 96.09 ± 20.38 kg,P < 0.001). Approximately 58% of all participants lost ≥5% of their initial body weight, and almost 55% remained above this threshold at 1 year. The incentive-motivated group lost more weight than the self-motivated group at the end of the program but did not lose any further weight, whereas the self-motivated group continued to lose weight. After 1 year, both groups had achieved the same weight loss. Conclusions: The cash reward program was effective in inducing short-term weight loss. The optimal duration for financial incentive-based programs in inducing a sustainable weight loss and their cost-effectiveness are important questions for further investigation.